Productivity of PT. Adira Dinamika Multifinance is Proven to be Influenced by The Work Environment and Motivation - Dadan Drajat Martamihardja; Uce Karna Suganda (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This study aims to analyze and describe the effect of the work environment and motivation on the productivity of PT. Adira Dinamika Multifinance in the Marketing department. The population and sample in this study were 46 respondents. The research method used in this study is a descriptive and verification research method using a quantitative approach, where the analysis uses the SPSS version 22 program package. R square 0.711 indicates that the simultaneous effect is 84.3% while the partial effect of the work environment has an effect on work productivity, as well as motivation, has an influence on the work productivity of PT. Adira Dynamics Multifinance